Hemodialysis Patient Preference for Type of Vascular Access: Variation and Predictors across Countries in the DOPPS. Issue 3 (July 2013) - Fissell, Rachel B.; Fuller, Douglas S.; Morgenstern, Hal; Gillespie, Brenda W.; Mendelssohn, David C.; Rayner, Hugh C.; Robinson, Bruce M.; Schatell, Dori; Kawanishi, Hideki; Pisoni, Ronald L.
Purpose: Catheters are associated with worse clinical outcomes than fistulas and grafts in hemodialysis (HD) patients. One potential modifier of patient vascular access (VA) use is patient preference for a particular VA type. The purpose of this study is to identify predictors of patient VA preference that could be used to improve patient care. Methods: This study uses a cross-sectional sample of data from the Dialysis Outcomes and Practice Patterns Study (DOPPS 3, 2005-09), that includes 3815 HD patients from 224 facilities in 12 countries. Using multivariable models we measured associations between patient demographic and clinical characteristics, previous catheter use and patient preference for a catheter. Results: Patient preference for a catheter varied across countries, ranging from 1% of HD patients in Japan and 18% in the United States, to 42% to 44% in Belgium and Canada. Preference for a catheter was positively associated with age (adjusted odds ratio per 10 years=1.14; 95% 0=1.02-1.26), female sex (OR 1.49; 95% 0=1.15-1.93), and former (OR=2.61; 95% 0=1.66-4.12) or current catheter use (OR=60.3; 95% 0=36.5-99.8); catheter preference was inversely associated with time on dialysis (OR per three years=0.90; 95% 0=0.82-0.97). Conclusions: Considerable variation in patient VA preference was observed across countries, suggesting that patient VA preference may be influenced by sociocultural factors and thus could be modifiable. Catheter preference was greatest among current and former catheter users, suggesting that one way to influence patient VA preference may be to avoid catheter use whenever possible.